HUBUNGAN KATARAK DENGAN INDEKS MASSA TUBUH - Mohammad Rizky Pratama (Universitas Muhammadiyah Yogyakarta, 2016)
Background : Cataract is an opacification of the lens that leads to decreased visual acuity and / or functional defects perceived by the patient. Cataract may cause of blindness and visual impairment in the world. In 2002, WHO estimated the number of cataract that resulted reversible blindness exceeds 17 million (47.8%) of the 37 million people of blindness in the world, and this figure is expected to reach 40 million by 2020. One of risk factor for cataract is obesity. This is bad news, because obesity rates in Indonesia is increase. Based on the results Riskesdas (2013), in adult males increased from 13.9% in 2007 to 19.7% in 2013. Whereas in adult women increased from 14.8% in 2007 to 32.9% in 2013. This study is required to determine the relationship between cataract and obesity Methods: The research was used observational analytic design with cross sectional approach. The sample of this research were 104 patients aged â‰¥ 40 years old in the village of Brajan, Kasihan, Bantul and Sleman Sedayu village who has been measuring height and weight, as well as the examination of cataracts.